Chemical constituents from roots of Garcinia mangostana (Linn.) - Sheikh Mohd Ghazali, Sheikh Ahmad Izaddin (Canadian Center of Science and Education, 2010)
Novel extraction studies on Garcinia mangostana roots was chemically investigated. Detail phytochemical studies on the roots of Garcinia mangostana have resulted in the isolation of six compounds. The structures of these compounds were elucidated using spectroscopic experiments namely NMR, IR, UV and MS. The root bark of Garcinia mangostana furnished six xanthones, ?-mangostin (1), ?-mangostin (2), ?-mangostin (3), garcinone-D (4), mangostanol (5), and gartanin (6).